2015
DOI: 10.1002/2015ja021652
|View full text |Cite
|
Sign up to set email alerts
|

NmF2 enhancement during ionospheric F2 region nighttime: A statistical analysis based on COSMIC observations during the 2007–2009 solar minimum

Abstract: In this paper the global features of NmF2 enhancement occurring during ionospheric F2 region nighttime (the period when the sunlight is occulted by the Earth in the altitudinal range of ionospheric F2 region) and lasting for more than 2 h were investigated based on Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) measurements during the 2007–2009 solar minimum. This nighttime enhancement of NmF2 mainly appears at the latitudes with dips larger than 45° in the winter hemisphere i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…Different mechanisms were proposed to explain this phenomenon, including plasmaspheric flux from the conjugate ionosphere (Evans, ), increased downward flux from the plasmasphere (e.g., Bailey et al, ; Jakowski & Forster, ), and enhanced meridional neutral wind (Mikhailov et al, ). Our analysis of TEC data following several SSW events indicates that on average a postmidnight increase in electron density is very strong at 75°W and maximizes at 30–33°N (Figure ), consistent with Constellation Observing System for Meteorology, Ionosphere, and Climate observations (Chen et al, ). During the SSW of 2013, the latitudinal peak in the postmidnight density increase shifted poleward by ~5–7°, leading to an increase in electron density and TEC at 40–50°N on 18 January 2013 (Figure ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Different mechanisms were proposed to explain this phenomenon, including plasmaspheric flux from the conjugate ionosphere (Evans, ), increased downward flux from the plasmasphere (e.g., Bailey et al, ; Jakowski & Forster, ), and enhanced meridional neutral wind (Mikhailov et al, ). Our analysis of TEC data following several SSW events indicates that on average a postmidnight increase in electron density is very strong at 75°W and maximizes at 30–33°N (Figure ), consistent with Constellation Observing System for Meteorology, Ionosphere, and Climate observations (Chen et al, ). During the SSW of 2013, the latitudinal peak in the postmidnight density increase shifted poleward by ~5–7°, leading to an increase in electron density and TEC at 40–50°N on 18 January 2013 (Figure ).…”
Section: Discussionsupporting
confidence: 89%
“…A postmidnight increase in midlatitude ionospheric electron density is a well‐documented phenomenon (e.g., Chen et al, ; Farelo et al, , and references therein). Different mechanisms were proposed to explain this phenomenon, including plasmaspheric flux from the conjugate ionosphere (Evans, ), increased downward flux from the plasmasphere (e.g., Bailey et al, ; Jakowski & Forster, ), and enhanced meridional neutral wind (Mikhailov et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…During solstice, midlatitude enhancements are observed in the winter hemisphere (Figure ), likely corresponding to the NWA feature (see Jakowski et al, , and the references therein). Another recent study used N m F 2 measurements from the COSMIC constellation to find that the enhancements maximize at the magnetic latitudes of about 40° –50° in the winter hemisphere (Chen et al, ). The CHAMP and DMSP density enhancements in general have consistent latitudinal structures.…”
Section: Discussionmentioning
confidence: 99%
“…Their simulation showed that nighttime enhancements of N m F 2 can occur when the plasmasphere becomes sufficiently full. Numerous experimental studies support the importance of the plasmaspheric flows for the formation of the nighttime electron density enhancements [e.g., Bertin and Papet‐Lepine , ; Davies et al ., ; Standley and Williams , ; Williams and Jain , ; Bailey et al ., ; Jakowski and Förster , ; Farelo et al ., ; Dabas and Kersley , ; Jakowski et al ., ; Chen et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of mathematical modeling studies of the coupling between the F region and the plasmasphere were published over the past 40 years [e.g., Moffett and Murphy, 1973;Banks, 1974, 1975;Marubashi and Grebowsky, 1976;Bailey et al, 1978Bailey et al, , 1979Marubashi, 1979;Murphy et al, 1979Murphy et al, , 1980Quegan et al, 1982;Nagmoosh and Murphy, 1983;Schunk, 1988;Mikhailov et al, 2000;Richards et al, 2000;Pavlov and Pavlova, 2005;Jee et al, 2005]. Williams and Jain, 1984;Bailey et al, 1991;Jakowski and Förster, 1995;Farelo et al, 2002;Dabas and Kersley, 2003;Jakowski et al, 2015;Chen et al, 2015].…”
Section: Introductionmentioning
confidence: 99%